Using Halophiles (Bacillus licheniformis) to Treat Spinetoram (pesticide) Contamination - Noaman, Hussein Khalid; Al-Mayaly, Ithar Kamel (Iraqi Journal of Science, 2024)
The present study aimed to identify Bacillus licheniformis in Iraqi environments and test their ability to degrade the pesticides usuallyed in agricultural fields. Three temperatures (25, 30, 35 oC) and pH values (5,7,9) were chose for this study, while three concentrations of above mentioned pesticide (600, 1200, 1800) ppm were used. 94% and 91% were achieved at pH values 9 and 7 at 35oC and 600 ppm.